Implementation of Interface between AXI and DDR3 memory Controller for SoC (International Journal of Engineering and Computer Science, 2015)
This paper describes the implementation of AXI compliant DDR3 memory controller. It discusses the overall architecture of the DDR3 controller along with the detailed design and operation of its individual sub blocks, the pipelining implemented in the design to increase the design throughput. It also discusses the advantage of DDR3 memories over DDR2 memories and the AXI protocol operation. The AXI DDR3 Controller provides access to DDR3 memory. It accepts the Read / Write commands from AXI and converts it into DDR3 access. While doing this it combines AXI burst transactions into single DDR access where ever possible to achieve the best possible performance from DDR3 memory subsystem. The AXI DDR3 Controller allows access of DDR3 memory through AXI Bus interface. The controller works as an intelligent bridge between the AXI host and DDR3 memory. It takes care of the DDR initialization and various timing requirements of the DDR3 memory. The controller implements multiple schemes to increases the effective memory throughput commands. It operates all the memory banks in parallel for attaining the maximum throughput from the memory and minimizes the effect of precharge /refresh and other DDR internal operations. Design is simulated in Modelsim 10.4a  and synthesis on Xilinx ISE tool to report the area ,power, and delay.